Safety and efficacy of combined acetabular reconstruction and microwave ablation in the treatment of periacetabular metastatic disease: a retrospective clinical evaluation - Zheng, Chuanxi; Qiu, Jin; Zhou, Xiayi; Xu, Gang; Lan, Tao (Frontiers in Oncology, 2024)
IntroductionThe periacetabular bone defects caused by metastatic disease often necessitate acetabular reconstruction and various techniques have been employed with varying degrees of success. The purpose of this study was to evaluate the efficacy and safety of acetabular reconstruction in conjunction with adjuvant microwave ablation as a surgical intervention for patients with periacetabular metastases.MethodsBetween January 2019 and September 2023, 17 consecutive patients with different tumor subtypes required surgical intervention for periacetabular metastases. The acetabular reconstruction was performed by utilizing an acetabular reconstructive cage and cement total hip arthroplasty with microwave ablation. A retrospective review was performed to assess pain relief, intraoperative details and postoperative complications. Functional status following procedures was determined by the 1993 Musculoskeletal Tumor Society (MSTS) score and the overall survival of patients was estimated by Kaplan-Meier analysisResultsIn total, 8 males and 9 females were included with an average age of 48.6 years (range 34-66). Patients reported a significant improvement in the level of pain and the mean VAS score declined from 7.7 preoperatively to 2.2 postoperatively. Of the 17 patients, 16 could ambulate either independently (6 patients) or using a walking aid (10 patients) with a mean MSTS score of 18.9. The median follow‐up was 9.0 months. Nine patients were alive at the most recent follow-up with overall survival of 40.9% at 12 months and 30.7% at 36 months, respectively.ConclusionIn selected patients with periacetabular metastasis, the utilization of an acetabular cage and cement total hip arthroplasty presents a less invasive reconstruction technique. The incorporation of adjuvant microwave ablation has shown promise in providing long-lasting pain relief, reducing intraoperative bleeding, and improving local tumor control. However, further research and extended follow-up are necessary to establish the effectiveness of this procedure.